2010
DOI: 10.1161/circulationaha.110.952820
|View full text |Cite
|
Sign up to set email alerts
|

CD69 Limits the Severity of Cardiomyopathy After Autoimmune Myocarditis

Abstract: Background-Experimental autoimmune myocarditis (EAM), a mouse model of post-infectious cardiomyopathy, reflects mechanisms of inflammatory cardiomyopathy in humans. EAM is characterized by an infiltration of inflammatory cells into the myocardium that can be followed by myocyte fibrosis, edema, and necrosis, leading to ventricular wall dysfunction and heart failure. Different data indicate that CD69 exerts an important immunoregulatory effect in vivo. However, the possible role of CD69 in autoimmune myocarditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 48 publications
2
57
0
3
Order By: Relevance
“…IL-17, a potent inflammatory cytokine, induces the expression of numerous proinflammatory cytokines, chemokines, and metalloproteinases, and plays a major role in neutrophil proliferation, survival, and chemotaxis [35,36]. Furthermore, some reports indicate that Th17 cells contribute to the pathogenesis of EAM [28,29,[37][38][39]. According to the above investigation, HMGB1 blockade attenuates cardiac pathological changes and reduces the number of infiltrating inflammatory cells (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…IL-17, a potent inflammatory cytokine, induces the expression of numerous proinflammatory cytokines, chemokines, and metalloproteinases, and plays a major role in neutrophil proliferation, survival, and chemotaxis [35,36]. Furthermore, some reports indicate that Th17 cells contribute to the pathogenesis of EAM [28,29,[37][38][39]. According to the above investigation, HMGB1 blockade attenuates cardiac pathological changes and reduces the number of infiltrating inflammatory cells (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, CD69 + T cells were found in the proximity of MAP2-immunoreactive cells in the stroke group. Previous studies showed that CD69 + T cells facilitated protective immune mechanisms including self-limited immune responses (30), lymphocyte retention in lymph nodes (31), and prevention of autoimmune reactions (32). In addition, CD69 exerted a negative regulation of allergen- induced T cell effector responses and prevented Th17 cell differentiation in allergic diseases (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CD69 exerted a negative regulation of allergen- induced T cell effector responses and prevented Th17 cell differentiation in allergic diseases (30). Accordingly, mice lacking CD69 had exacerbated forms of arthritis, contact dermatitis, allergic asthma, and autoimmune myocarditis (31,32). Although our study does not demonstrate the direct activation of T cells by CD69 or its effects, we can hypothesize that the abundant expression of CD69 + T cells in the proximity of neuroantigenimmunoreactive APCs resulted in a tighter regulation of harmful autoimmune responses.…”
Section: Discussionmentioning
confidence: 99%
“…CD69 is also involved in regulation of T and B lymphocyte egress from secondary lymphoid tissues by blocking the spingosine 1-phosphate 1 receptor (16). Recent work in mice indicates a role of CD69 in the regulation of arthritis (17,18), asthma (19,20), myocarditis (21), pathogen clearance (22), and tumor immunity (23,24). CD69 surface expression is upregulated by lymphocytes at mucosal sites such as intraepithelial and lamina propria (LP) lymphocytes (25,26).…”
mentioning
confidence: 99%